Utilización de diferentes niveles de cúrcuma (Curcuma longa) 0.5; 1 y 1.5 % para la pigmentación de la carne de pollos de engorde - Paz Segovia, Camila Mishell (2020)
This work presents the evaluation of the use of different levels of turmeric for the meat pigmentation of broilers as an option to replace artificial pigmentants. In this study, 100 one-day-old broilers of the Cobb500, line were used, these were randomly distributed in 4 groups made up of 25 birds each and 5 repetitions per group: basal diet (control-T0), basal diet + 0.5% of turmeric flour (T1), basal diet + 1% turmeric flour (T2) and basal diet + 1.5% turmeric flour (T3). In the first place, the bromatological characterization of the turmeric flour, obtained from the rhizomes of the plant, was carried out to verify its composition and properties. The study lasted 49 days and weekly data on weight, food consumption, among others, were collected for subsequent analysis. In the results analysis stage, different productive parameters were calculated to assess the response in broilers when consuming turmeric flour as an additive in their diet, thus, the feeding efficiency and the validity of the diet have been evidenced for its use in the productive process, in addition, the resulting pigmentation has been evaluated, like main objective of this study. Subsequently, an ANOVA and Duncan test were used to determine to what extent the applied treatments differ and the most effective was established from the data collected in the broilers rearing stages. Then, through a laboratory analysis, the quality of the broiler carcass was determined for each treatment and thus it was verified which of these is more viable. Finally, the conclusions and recommendations regarding this study are presented, taking into account the results obtained